METABOLICALLY HEALTHY AND UNHEALTHY OBESITY IN CHILDREN FROM THE POINT OF VIEW OF EVIDENCE-BASED MEDICINE - V. Furdela; I. Smiian; M. Furdela (Східноукраїнський медичний журнал, 2020)
Introduction. Childhood obesity and associated metabolic comorbidities is a major global health concern. Metabolic syndrome (MS) is a cluster of metabolic abnormalities that confers a substantial increase in cardiovascular disease risk. In the context of the childhood obesity pandemic, a distinct subgroup of youth with obesity less prone to the development of metabolic disturbances, called “metabolically healthy obese” (MHO), recently has come into focus. However, the diagnostic criteria of both conditions are still controversial in children. Therefore, the purpose of our research is to estimate the prevalence of metabolic syndrome and metabolically healthy obesity in school-age boys using international reference standards and to recognize the most sensitive metabolic markers.